The ghost of Brennus - Diskin, Matthew J. (Trinity College (Dublin, Ireland). Department of Classics, 2011)
In this dissertation, I trace the origin and the evolution of the use of terms like "Kελτοι" and "Γαλαται" in Greek ethnographic and/or historical texts from the works of Herodotus and Hecataeus into the Roman period. More detailed textual analyses are undertaken of parts of the works of major authors who influenced or were strongly influenced by Latin discourse on the Celts or Gauls, principally Polybius, Diodorus, Strabo and Plutarch. I also discuss more general themes directly or indirectly relevant to Roman attitudes towards Gauls, such as Hyperborean myths and theories of environmental deteminism.
Keywords: Classics, Ph.D.; Ph.D. Trinity College Dublin